Identification and characterization of two RNA silencing suppressors encoded by ophioviruses - Robles Luna, Gabriel (2017)
Citrus psorosis virus and Mirafiori lettuce big-vein virus are two members of the genus Ophiovirus, family Ophioviridae. So far, how these viruses can interfere in the antiviral RNA silencing pathway is not known. In this study, using a local GFP silencing assay on Nicotiana benthamiana, the 24K-25K and the movement protein (MP) of both viruses were identified as RNA silencing suppressor proteins. Upon their co-expression with GFP in N. benthamiana 16c plants, the proteins also showed to suppress systemic RNA (GFP) silencing. The MPCPsV and 24KCPsV proteins bind long (114 nucleotides) but not short-interfering (21 nt) dsRNA, and upon transgenic expression, plants showed developmental abnormalities that coincided with an altered miRNA accumulation pattern. Furthermore, both proteins were able to suppress miRNA-induced silencing of a GFP-sensor construct and the co-expression of MPCPsV and 24KCPsV exhibited a stronger effect, suggesting they act at different stages of the RNAi pathway.